Storm surge-driven salinization mechanisms in coastal aquifers: Insights from 2D and 3D modelling in southwestern Bangladesh - ChiSan Tsai; Sean E. Feist; Mohammad A. Hoque; Kazi Matin Ahmed; Adrian P. Butler (Advances in Water Resources, 2026)

Chiari I Malformation as a Human Disease Model of Cerebellar Cognitive–Affective Dysfunction - William Davalan; William E. Butler; Jeremy D. Schmahmann; William Muñoz; Neel H. Mehta; Angelique C. Paulk; Kristopher T. Kahle (The Cerebellum, 2026)

Automated 24-h cattle feeding behaviour analysis using Raspberry Pi, infrared imaging, and deep learning-based head position and ID classification - G. Wager-Jones; M. Butler; W.E. Harris; M. Rutter; E. Bleach; K. Behrendt (Biosystems Engineering, 2026)

Chilling Consequences: Recruitment Failure of Four Native Fish Species in a Thermally Polluted, Regulated River - Laura E. Michie; James N. Hitchcock; Simon M. Mitrovic; Matthew Gordos; Gavin L. Butler (Fisheries Management and Ecology, 2026)
Cold water pollution (CWP), caused by the release of unseasonably cool water from the bottom of large reservoirs to downstream rivers, is an escalating global threat to riverine biodiversity that is exacerbated by future dam developments and climate change. This study examined the impact of CWP on native fish populations in the Severn River (NSW, Australia), downstream of a large reservoir. Long‐term data (2012–2024) revealed chronic CWP, with thermal regimes frequently below thresholds required for native fish spawning during the austral summer period. An aged population structure and chronic recruitment failure were evident in four native fish species. Additionally, native fish stocking efforts have resulted in limited success. We recommend both long‐term CWP mitigation and immediate adaptive management strategies, such as optimising stocking practices and opportunistic water management actions, as critical to sustaining native fish populations.

Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

A pragmatic framework for local operationalisation of national-level biodiversity impact mitigation commitments - Thomas B. Atkins; Natalie E. Duffus; Amber J. Butler; Hannah C. Nicholas; Sophus O.S.E. zu Ermgassen; Prue Addison; E.J. Milner-Gulland (Environmental Science & Policy, 2025)

Decoy oligonucleotides targeting NF-κB: a promising therapeutic approach for inflammatory diseases - Maryam Mahjoubin-Tehran; Samaneh Rezaei; Alexandra E. Butler; Amirhossein Sahebkar (Inflammation Research, 2025)

Statins and adhesion molecules: a review of a novel pleiotropic property of statins - Mahvash Sadeghi; Sajad Dehnavi; Sanaz Keshavarz Shahbaz; Khadijeh Koushki; Alexandra E. Butler; Tannaz Jamialahmadi; Amirhossein Sahebkar (Immunologic Research, 2025)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Unmet needs among long-term breast cancer survivors - Rina A. Yarosh; Hazel B. Nichols; Rachel Hirschey; Erin E. Kent; Deborah K. Mayer; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2025)

Competition for waterborne food resources among tropical shallow‐water sponges - Mark J. Butler; Steven E. McMurray; Joseph R. Pawlik (Ecology, 2025)
A recurrent theme in marine ecology is that the community dynamics of sessile, suspension‐feeding animals is primarily limited by the availability of space, but in some habitats, filtration by these organisms may locally deplete water column resources, setting the stage for exploitative competition for food. We examined filtration by sponge assemblages in the shallow waters (~2 m depth) of Florida Bay (Florida, USA), where water residence times are often high and filtration by dense communities of sponges was hypothesized to deplete the water column of food, primarily picoplankton and dissolved organic matter (DOM). We transplanted three sponge species into replicate locations that differed by an order of magnitude in natural sponge community biomass. Sponge transplants were clones, enabling us to control for sponge genotype effects across all sites. The growth of sponge clones was recorded seasonally for 18–30 months. Growth of transplants placed in areas devoid of sponges was 10 times greater than growth in areas with dense sponge communities and three times greater than growth in areas with average sponge biomass. Sponge mortality was similar regardless of background sponge density. Measurements of picoplankton, DOM, and PO 4 concentration confirmed an inverse relationship with sponge community biomass, whereas nitrogen concentrations in seawater were highest where sponge species replete with nitrogen‐fixing symbiotic microbial communities were most abundant. This is striking evidence that filtration of waterborne resources by sponges in shallow, coastal environments can deplete those resources sufficiently to cause exploitative competition that limits sponge growth.

Controls on shear band orientation in deforming porous rocks: Insights from improved microcrack segmentation method - Claudia Elijas-Parra; Alexis Cartwright-Taylor; Ian G. Main; Rebeca E. Ursu; Ian B. Butler; Florian Fusseis (Journal of Structural Geology, 2025)

Are geological description practices and classification schemes fit for future use? Breccias as an example - Stephanie Flude; Clare E. Bond; Robert W.H. Butler (Earth-Science Reviews, 2025)

Investigating ozone build-up in the east of England during the July 2015 heat wave - Johana Romero-Alvarez; Aurelia Lupaşcu; Steve Dorling; Claire E. Reeves; Tim Butler (Science of The Total Environment, 2025)

Regulatory effect of curcumin on CD40:CD40L interaction and therapeutic implications - Fatemeh Askarizadeh; Alexandra E. Butler; Prashant Kesharwani; Amirhossein Sahebkar (Food and Chemical Toxicology, 2025)

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

TLR/NLRP3 inflammasome signaling pathways as a main target in frailty, cachexia and sarcopenia - Sanaz Keshavarz Shahbaz; Aida Mokhlesi; Roghaye Keshavarz Sadegh; Kimia Rahimi; Tannaz Jamialahmadi; Alexandra E. Butler; Prashant Kesharwani; Amirhossein Sahebkar (Tissue and Cell, 2025)

Allometric aboveground biomass equations to quantify carbon content of Southeast Australian saltmarsh vegetation - Jami Butler; Clare Duncan; Paul E. Carnell; Anirban Akhand; Stacey M. Trevathan-Tackett; Peter I. Macreadie (Regional Studies in Marine Science, 2025)

Targeting mTOR with curcumin: therapeutic implications for complex diseases - Danial Khayatan; Seyed Mehrad Razavi; Zahra Najafi Arab; Hadis Nasoori; Abtin Fouladi; Aytak Vahdat Khajeh Pasha; Alexandra E. Butler; Sercan Karav; Saeideh Momtaz; Amir Hossein Abdolghaffari; Amirhossein Sahebkar (Inflammopharmacology, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Environmental visual complexity increases the foraging success of mesopredators by promoting explorative behaviours - Samuel R. Matchette; Samuel J. Butler; Charles E. Redfern Llanos; James E. Herbert-Read (Animal Behaviour, 2025)

Multi-layers: Do incompetent horizons always act as thrust flats? - Clare E. Bond; Francisca Robledo; Robert W.H. Butler (Journal of Structural Geology, 2025)

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

The analgesic effect of curcumin and nano-curcumin in clinical and preclinical studies: a systematic review and meta-analysis - Pooya Hajimirzaei; Hossein Eyni; Maryam Razmgir; Sajad Abolfazli; Simin Pirzadeh; Faeze Sadat Ahmadi Tabatabaei; Ayda Vasigh; Nafiseh Yazdanian; Fatemeh Ramezani; Atousa Janzadeh; Alexandra E. Butler; Amirhossein Sahebkar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Evaluating the sensitivity of a chronic plant bioassay relative to an independently derived predicted no-effect thresholds to support risk assessment of very hydrophobic organic chemicals - Aaron D. Redman; Miriam Leon Paumen; Daniel J. Letinski; Barbara A. Kelley; Cary Sutherland; Bryan M. Hedgpeth; Josh D. Butler; Roger Prince; Gail E. Bragin; Abraham J. Smith (Archives of Environmental Contamination and Toxicology, 2025)

Harvest trends, growth and longevity, and population dynamics reveal traditional assumptions for redhorse (Moxostoma spp.) management in Minnesota are not supported - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Allen H. Andrews; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Gelation and large thermoresponse of cranberry-based xyloglucan - Aniruddha Kulkarni; Stephen Michel; Jason E. Butler; Kirk J. Ziegler (Carbohydrate Polymers, 2024)

Colony life history of the tropical arboreal ant, Cephalotes goniodontus De Andrade, 1999 - I. A. E. Butler; T. Butterfield; M. Janda; D. M. Gordon (Insectes Sociaux, 2024)
Arboreal ants are ecologically important in tropical forests, but there are few studies using DNA markers to examine their population and colony structure. Colonies of the arboreal turtle ant Cephalotes goniodontus create trail networks through the canopy of the tropical forest, in dense vegetation where it is difficult to determine how long a nest is used and how neighboring colonies partition space. We monitored 53 nest sites for up to six years and, using seven microsatellite markers, genotyped samples of workers collected at or near 41 nests over 1–4 years. We calculated average relatedness within samples collected at a given location, and between samples collected at the same location in successive years, and performed pedigree analysis to predict the number of queens that produced each sample of workers. Fifteen samples were highly related ( r ≥ 0.6) from single colonies, of which 11 were monogynous and the remaining four had two queens; 19 were of intermediate relatedness (0.1 ≤ r < 0.6) with 1–6 queens, and 7 were groups of unrelated workers (r < 0.1) from at least 4 queens. Colonies persisted at the same nest site for 2–6 years. The smallest distance we found separating nests of different colonies was 16.2 m. It appears that different colonies may share foraging trails. Our study demonstrates the feasibility of using a cost-efficient genotyping method to provide information on colony structure and life history of ant species.

Ramps first – Interpreting thrust nucleation in multilayers - Phoebe R. Sleath; Clare E. Bond; Robert W.H. Butler (Journal of Structural Geology, 2024)

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Quantifying myelin density in the feline auditory cortex - Austin Robertson; Daniel J. Miller; Adam Hull; Blake E. Butler (Brain Structure and Function, 2024)

Pleistocene shifts in Great Basin hydroclimate seasonality govern the formation of lithium-rich paleolake deposits - Tripti Bhattacharya; Peter R. Brennan; Daniel E. Ibarra; Catherine A. Gagnon; Kristina L. Butler; Alexa Terrazas; Shaw Miller; Lee Ann Munk; David F. Boutt; Ran Feng; Stephanie N. Bullinger; Lucy Weisbeck (Quaternary Science Reviews, 2024)

Curcumin and Ferroptosis: a Promising Target for Disease Prevention and Treatment - Zahra Foroutan; Alexandra E. Butler; Gokhan Zengin; Amirhossein Sahebkar (Cell Biochemistry and Biophysics, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Microwave spectra of the leading and trailing hemispheres of Iapetus - Léa E. Bonnefoy; Emmanuel Lellouch; Alice Le Gall; Jean-François Lestrade; Raphaël Moreno; Bryan Butler; Jérémie Boissier; Cédric Leyrat; Robin Sultana; Thibault Cavalié; Mark Gurwell; Arielle Moullet; et al. (Icarus, 2024)

Critical Review of Field Studies of Chemical Surface Coatings to Mitigate Leaching from Mining Wastes - Barbara A. Butler; Lauren E. Brase (Mine Water and the Environment, 2024)

Relationship between endocrine disrupting chemicals (phthalate metabolites, triclosan and bisphenols) and vitamin D in female subjects: An exploratory pilot study - Edwina Brennan; Alexandra E. Butler; Manjula Nandakumar; Kristie Thompson; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2024)

Insights into the evolution of the eucalypt CER1 and CER3 genes involved in the synthesis of alkane waxes - Mariano A. Hernández; René E. Vaillancourt; Brad M. Potts; Jakob B. Butler (Tree Genetics & Genomes, 2024)
The genes ECERIFERUM1 ( CER1 ) and ECERIFERUM3 ( CER3 ) encode the biosynthesis of alkane waxes, a key component of the plant cuticle. To study the evolution of CER1 and CER3 in a highly diverse group of eucalypts, we performed a genome-wide survey using recently released genome assemblies of 28 Myrtaceae species, with 22 species from the main eucalypt lineage and 6 non-eucalypt Myrtaceae tree species. We manually annotated 250 genes and pseudogenes, identifying a near-ubiquitous single copy of CER3 and 2 to 10 CER1 gene copies per Myrtaceae species. Phylogenetic analysis suggested that copy number variation in eucalypts is due to multiple tandem duplication events, both ancient (shared by all Myrtaceae species studied) and relatively recent (present only in eucalypts). Inter-chromosomal translocations were discovered for both CER1 and CER3 , along with recurrent loss of often the same CER1 introns in the WAX2 domain, the domain that is essential for wax production. Despite the varied environments occupied by the eucalypt species in this study, we did not find statistically significant associations between intra-genic structural changes or CER1 copy number and aspects of the environment they occupy (including aridity). The challenge is now to explain the species-specific evolutionary histories that contributed to the observed variation in CER1 and the extent to which it may contribute to the adaptability of eucalypts.

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Mapping faults in 3D seismic data – why the method matters - Francisca Robledo Carvajal; Robert W.H. Butler; Clare E. Bond (Journal of Structural Geology, 2023)

Assessing pore network heterogeneity across multiple scales to inform CO2 injection models - Shane K. Butler; César Barajas-Olalde; Xue Yu; Matthew E. Burton-Kelly; Blaise A.F. Mibeck; Lingyun Kong; Bethany A. Kurz; Dustin Crandall (International Journal of Greenhouse Gas Control, 2023)

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Impact of dairy farms on groundwater quality in a productive basin in the northeast of the Pampean Plain, Argentina - F. Cellone; L. Santucci; G. Borzi; C. Tanjal; C. Di Lello; L. Butler; J. Córdoba; L. Lamarche; J. Galliari; E. Melendi; M.I. Delgado; E. Carol (Groundwater for Sustainable Development, 2023)

Validation of load based testing methodology for residential air conditioners and heat pumps - Parveen Dhillon; Drew Welch; Brian Butler; W. Travis Horton; James E. Braun (Energy and Buildings, 2023)

Association of flame retardants, polybrominated diethyl ethers (PBDEs), with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2023)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

Impact of curcumin on p38 MAPK: therapeutic implications - Hedieh Sadat Shamsnia; Mahtab Roustaei; Danial Ahmadvand; Alexandra E. Butler; Dorsa Amirlou; Sanam Soltani; Saeideh Momtaz; Tannaz Jamialahmadi; Amir Hossein Abdolghaffari; Amirhossein Sahebkar (Inflammopharmacology, 2023)

Intuitive Eating or Mindfulness in Eating Disorder Treatment: A Literature Review - S. Butler; E. Metallinos-Katsaras (Journal of the Academy of Nutrition and Dietetics, 2023)

Association of polychlorinated biphenyls with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Environmental Research, 2023)

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

The Joy of birds: the effect of rating for joy or counting garden bird species on wellbeing, anxiety, and nature connection - Maria E. White; Iain Hamlin; Carly W. Butler; Miles Richardson (Urban Ecosystems, 2023)
The feeding of garden birds is a popular and accessible means of connecting with wildlife in urban environments in the United Kingdom. Past research has found that the main motivations for feeding birds are psychological benefits, concern for bird welfare, and connecting to nature. This study explores whether a brief birdwatching activity impacts on wellbeing, anxiety, and nature connection. One hundred and fifty-six participants took part in a birdwatching activity, identifying the species that entered their garden during a thirty-minute period. Participants were randomly allocated to the ‘joy’ group, who rated their feeling of joy on seeing each species, or the ‘count’ group, who counted the number of birds of each species. Measures of wellbeing, state anxiety and nature connection were completed before and after the observation period. Both groups had improved wellbeing, anxiety, and nature connection, though decreases in anxiety were greatest for those in the joy group. These results suggest that activating a sense of joy heightens the psychological benefits of watching garden birds. These benefits and the strengthening of nature connections highlight the reciprocal relationship between humans and birds and the importance of actions towards healthy, sustainable urban ecosystems.

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

The condition, use and future of the UK's largest accessible dinosaur tracksite at Spyway Quarry, Dorset - Kirsty M. Edgar; Luke E. Meade; Harry T. Jones; Lewis Haller; Sam Scriven; Christopher Reedman; Richard J. Butler (Proceedings of the Geologists' Association, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Adaptation pathways to inform policy and practice in the context of development - Edward Sparkes; Edmond Totin; Saskia E. Werners; Russell M. Wise; James R.A. Butler; Katharine Vincent (Environmental Science & Policy, 2023)

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

Otoliths suggest lifespans more than 30 years for free‐living bowfin Amia calva : Implications for fisheries management in the bowfishing era - Alec R. Lackmann; Ewelina S. Bielak‐Lackmann; Malcolm G. Butler; Mark E. Clark (Journal of Fish Biology, 2022)
The bowfin Amia calva is an amiid (Amiiformes) relict native to North America. It is the last surviving member of the Halecomorphi, a group of fishes that evolved more than 250 million years ago. Despite the phylogenetic significance of the amiids in vertebrate evolution, little has been published about their age and growth. Recreational bowfin harvest is currently unregulated throughout most of the USA, yet new recreational fisheries are emerging. As such, bowfin are increasingly harvested by sport bowfishing without limit, in addition to their growing commercial harvest for caviar. From 2017 to 2021 we studied a total of 81 bowfin from 11 populations across the east–west gradient of Minnesota within a narrow latitudinal margin (

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Review on Fixed and Floating Offshore Structures. Part I: Types of Platforms with Some Applications - Chiemela Victor Amaechi; Ahmed Reda; Harrison Obed Butler; Idris Ahmed Ja’e; Chen An (Journal of Marine Science and Engineering, 2022)
Diverse forms of offshore oil and gas structures are utilized for a wide range of purposes and in varying water depths. They are designed for unique environments and water depths around the world. The applications of these offshore structures require different activities for proper equipment selection, design of platform types, and drilling/production methods. This paper will provide a general overview of these operations as well as the platform classifications. In this paper, a comprehensive review is conducted on different offshore petroleum structures. This study examines the fundamentals of all types of offshore structures (fixed and floating), as well as the applications of these concepts for oil exploration and production. The study also presents various design parameters for state-of-the-art offshore platforms and achievements made in the industry. Finally, suitable types of offshore platforms for various water depths are offered for long-term operations. An extension of this study (Part II) covers sustainable design approaches and project management on these structures; this review helps designers in understanding existing offshore structures, and their uniqueness. Hence, the review also serves as a reference data source for designing new offshore platforms and related structures.

Otolith allometry informs age and growth of long-lived Quillback Carpiodes cyprinus - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2022)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Review on Fixed and Floating Offshore Structures. Part II: Sustainable Design Approaches and Project Management - Chiemela Victor Amaechi; Ahmed Reda; Harrison Obed Butler; Idris Ahmed Ja’e; Chen An (Journal of Marine Science and Engineering, 2022)
Offshore structures exist in a variety of forms, and they are used for a variety of functions in varied sea depths. These structures are tailored for certain environments and sea depths. Different actions for suitable equipment selection, platform type design, and drilling/production processes are required for the applications of these offshore structures, as given in Part I. This paper is the second part, which outlines various processes, loads, design approaches and project management of offshore platforms. To achieve these, proper planning must be conducted for lifting, transportation, installation, design, fabrication, and commissioning of these offshore platforms. Some historical developments of some offshore structures are presented, and some project planning routines are undertaken in this research. The ultimate goal is to provide a general overview of the many processes of offshore platform design, construction, loadout, transportation, and installation. Some discussions on the design parameters such as water depth and environmental conditions were presented. It also lists various software programs used in engineering designs covering software programs for structural analysis, 3D rendering, computer-aided design (CAD), hydrodynamic design, oceanic flow analysis, offshore structures analysis, mathematical modelling, coding/algorithm development software, and programming software to aid analytical calculations. The review also includes information on cutting-edge offshore platforms and industry advancements. Ultimately, for long-term operations, various types of offshore platforms for specific seawater depths are available.

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Differential vulnerability of native and non-native mollusks to predation by juvenile black carp - Anthony P. Porreca; Steven E. Butler; Jeremy S. Tiemann; Joseph J. Parkos (Biological Invasions, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Hares in the long grass: increased aircraft related mortality of the Irish hare (Lepus timidus hibernicus) over a 30-year period at Ireland’s largest civil airport - Samantha Ball; Fidelma Butler; Anthony Caravaggi; Neil E. Coughlan; Gerry Keogh; Michael J. A. O’Callaghan; Ricky Whelan; Thomas C. Kelly (European Journal of Wildlife Research, 2021)
Collisions between wildlife and aircraft are a serious and growing threat to aviation safety. Understanding the frequency of these collisions, the identity of species involved, and the potential damage that can be inflicted on to aircraft aid mitigation efforts by airfield managers. A record of all animal carcasses recovered from Dublin International Airport, Ireland’s largest civil aviation airport, has been maintained since 1990 where strikes with the endemic Irish hare ( Lepus timidus hibernicus ), a protected subspecies of mountain hare, are of particular concern despite substantial management efforts from the airfield authority. The first strike event with a hare was recorded in 1997, and strike events have substantially increased since then, with a sharp increase recorded in 2011. Over a 30-year period, a total of 320 strike events with the Irish hare have been recorded at the airfield. To date, no strike event with a hare has resulted in damage to an aircraft. However, carcasses can present as a major attraction to avian scavenger species in addition to posing as a risk of causing foreign object damage in the event of an undetected carcass. Hare strikes are discussed in the context of the rate of civil aircraft movements, possible direct and indirect damage to aircraft, and airfield wildlife hazard management. Here, we demonstrate that not only are strike events increasing by 14% on an annual basis, but that the kinetic energy of such an event has the potential to cause significant damage to an aircraft.

Hearing loss and brain plasticity: the hyperactivity phenomenon - Björn Herrmann; Blake E. Butler (Brain Structure and Function, 2021)

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Enhanced light interception and light use efficiency explain overyielding in young tree communities - Laura J. Williams; Ethan E. Butler; Jeannine Cavender‐Bares; Artur Stefanski; Karen E. Rice; Christian Messier; Alain Paquette; Peter B. Reich (Ecology Letters, 2021)
Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here we investigated whether light interception alone or in combination with light use efficiency (LUE) of dominant and subordinate species explained greater productivity of mixtures relative to monocultures (i.e. overyielding) in 108 young experimental tree communities. We found mixed‐species communities that intercepted more light than their corresponding monocultures had 84% probability of overyielding. Enhanced LUE, which arose via several pathways, also mattered: the probability of overyielding was 71% when, in a mixture, species with higher ‘inherent’ LUE (i.e. LUE in monoculture) intercepted more light than species with lower LUE; 94% when dominant species increased their LUE in mixture; and 79% when subordinate species increased their LUE. Our results suggest that greater light interception and greater LUE, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Stage‐dependent effects of river flow and temperature regimes on the growth dynamics of an apex predator - Rick J. Stoffels; Kyle E. Weatherman; Nick R. Bond; John R. Morrongiello; Jason D. Thiem; Gavin Butler; Wayne Koster; R. Keller Kopf; Nicole McCasker; Qifeng Ye; Brenton Zampatti; Ben Broadhurst (Global Change Biology, 2020)
In the world's rivers, alteration of flow is a major driver of biodiversity decline. Global warming is now affecting the thermal and hydrological regimes of rivers, compounding the threat and complicating conservation planning. To inform management under a non‐stationary climate, we must improve our understanding of how flow and thermal regimes interact to affect the population dynamics of riverine biota. We used long‐term growth biochronologies, spanning 34 years and 400,000 km 2 , to model the growth dynamics of a long‐lived, apex predator (Murray cod) as a function of factors extrinsic (river discharge; air temperature; sub‐catchment) and intrinsic (age; individual) to the population. Annual growth of Murray cod showed significant, curvilinear, life‐stage‐specific responses to an interaction between annual discharge and temperature. Growth of early juveniles (age 1+ and 2+ years) exhibited a unimodal relationship with annual discharge, peaking near median annual discharge. Growth of late juveniles (3+ to 5+) and adults (>5+) increased with annual discharge, with the rate of increase being particularly high in adults, whose growth peaked during years with flooding. Years with very low annual discharge, as experienced during drought and under high abstraction, suppress growth rates of all Murray cod life‐stages. Unimodal relationships between growth and annual temperature were evident across all life stages. Contrary to expectations of the Temperature Size Rule, the annual air temperature at which maximum growth occurred increased with age. The stage‐specific response of Murray cod to annual discharge indicates that no single magnitude of annual discharge is optimal for cod populations, adding further weight to the case for maintaining and/or restoring flow variability in riverine ecosystems. With respect to climate change impacts, on balance our results indicate that the primary mechanism by which climate change threatens Murray cod growth is through alteration of river flows, not through warming annual mean temperatures per se.

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Judgements of hand location and hand spacing show minimal proprioceptive drift - Alex Rana; Annie A. Butler; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2020)

Metal ions and graphene-based compounds as alternative treatment options for burn wounds infected by antibiotic-resistant Pseudomonas aeruginosa - Nathalie Karaky; Andrew Kirby; Andrew J. McBain; Jonathan A. Butler; Mohamed El Mohtadi; Craig E. Banks; Kathryn A. Whitehead (Archives of Microbiology, 2020)
Burn infections caused by Pseudomonas aeruginosa pose a major complication in wound healing. This study aimed to determine the antimicrobial effect of metal ions, graphene (Gr), and graphene oxide (GO), individually and in combination, against the planktonic and biofilm states of two antimicrobially resistant clinical strains of P. aeruginosa each with different antibiotic resistance profiles. Minimum inhibitory, minimum bactericidal, and fractional inhibitory concentrations were performed to determine the efficacy of the metal ions and graphene composites individually and their synergy in combination. Crystal violet biofilm and XTT assays measured the biofilm inhibition and metabolic activity, respectively. Molybdenum, platinum, tin, gold, and palladium ions exhibited the greatest antimicrobial activity (MIC = 7.8–26.0 mg/L), whilst GO and Gr demonstrated moderate-to-no effect against the planktonic bacterial cells, irrespective of their antibiograms. Biofilms were inhibited by zinc, palladium, silver, and graphene. In combination, silver–graphene and molybdenum–graphene inhibited both the planktonic and biofilm forms of the bacteria making them potential candidates for development into topical antimicrobials for burns patients infected with antibiotic-resistant P. aeruginosa .

Draft Genome Sequence of the Yeast Kazachstania telluris CBS 16338 Isolated from Forest Soil in Ireland - Florent Morio; Caoimhe E. O’Brien; Geraldine Butler (Mycopathologia, 2020)

Adipose derived stem cells and platelet rich plasma improve the tissue integration and angiogenesis of biodegradable scaffolds for soft tissue regeneration - N. Naderi; M. F. Griffin; A. Mosahebi; P. E. Butler; A. M. Seifalian (Molecular Biology Reports, 2020)
Current surgical reconstruction for soft tissue replacement involves lipotransfer to restore soft tissue replacements but is limited by survival and longevity of the fat tissue. Alternative approaches to overcome these limitations include using biodegradable scaffolds with stem cells with growth factors to generate soft tissue. Adipose derived stem cells (ADSCs) offer great potential to differentiate into adipose, and can be delivered using biodegradable scaffolds. However, the optimal scaffold to maximise this approach is unknown. This study investigates the biocompatibility of nanocomposite scaffolds (POSS-PCL) to deliver ADSCs with and without the addition of growth factors using platelet rich plasma (PRP) in vivo. Rat ADSCs were isolated and then seeded on biodegradable scaffolds (POSS-PCL). In addition, donor rats were used to isolate PRP to modify the scaffolds. The implants were then subcutaneously implanted for 3-months to assess the effect of PRP and ADSC on POSS-PCL scaffolds biocompatibility. Histology after explanation was examined to assess tissue integration (H&E) and collagen production (Massons Trichome). Immunohistochemistry was used to assess angiogenesis (CD3, α-SMA), immune response (CD45, CD68) and adipose formation (PPAR-γ). At 3-months PRP-ADSC-POSS-PCL scaffolds demonstrated significantly increased tissue integration and angiogenesis compared to PRP, ADSC and unmodified scaffolds (p < 0.05). In addition, PRP-ADSC-POSS-PCL scaffolds showed similar levels of CD45 and CD68 staining compared to unmodified scaffolds. Furthermore, there was increased PPAR-γ staining demonstrated at 3-months with PRP-ADSC-POSS-PCL scaffolds (p < 0.05). POSS-PCL nanocomposite scaffolds provide an effective delivery system for ADSCs. PRP and ADSC work synergistically to enhance the biocompatibility of POSS-PCL scaffolds and provide a platform technology for soft tissue regeneration.

Breast Reconstruction with a Tissue Engineering and Regenerative Medicine Approach (Systematic Review) - E. Donnely; M. Griffin; P. E. Butler (Annals of Biomedical Engineering, 2020)
Current techniques for breast reconstruction include an autologous-tissue flap or an implant-based procedure, although both can impose further morbidity. This systematic review aims to explore the existing literature on breast reconstruction using a tissue engineering approach; conducted with the databases Medline and Embase. A total of 28 articles were included, mainly comprising of level-5 evidence with in vitro and animal studies focusing on utilizing scaffolds to support the migration and growth of new tissue; scaffolds can be either biological or synthetic. Biological scaffolds were composed of collagen or a decellularized tissue matrix scaffold. Synthetic scaffolds were primarily composed of polymers with customisable designs, adjusting the internal morphology and pore size. Implanting cells, including adipose-derived stem cells, with combined use of basic fibroblast growth factor has been studied in an attempt to enhance tissue regeneration. Lately, a level-4 evidence human case series was reported; successfully regenerating 210 mL of tissue using an arterio-venous pedicled fat flap within a tissue engineering chamber implanted on the chest wall. Further research is required to evaluate whether the use of cells and other growth factors could adjust the composition of regenerated tissue and improve vascularity; the latter a major limiting factor for creating larger volumes of tissue.

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Independent QTL underlie resistance to the native pathogen Quambalaria pitereka and the exotic pathogen Austropuccinia psidii in Corymbia - Jakob B. Butler; Brad M. Potts; René E. Vaillancourt; David J. Lee; Geoff S. Pegg; Jules S. Freeman (Tree Genetics & Genomes, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Expression and localization of transient receptor potential channels in the bovine uterus epithelium throughout the estrous cycle - Maryam Ghavideldarestani; Alexandra E. Butler; Sadegh Shirian; Stephen L. Atkin (Molecular Biology Reports, 2019)

The hidden hand is perceived closer to midline - Hassan G. Qureshi; Annie A. Butler; Graham K. Kerr; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Genetic mapping of a barley leaf rust resistance gene Rph26 introgressed from Hordeum bulbosum - Xiaohui Yu; Hoi Yee Kong; Vijitha Meiyalaghan; Seona Casonato; Soonie Chng; E. Eirian Jones; Ruth C. Butler; Richard Pickering; Paul A. Johnston (Theoretical and Applied Genetics, 2018)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Evaluating the effects of catch-and-release angling on Cape stumpnose Rhabdosargus holubi in a South African estuary - NK Arkert; A-R Childs; MC Parkinson; AC Winkler; E Butler; S Mannheim; WM Potts (African Journal of Marine Science, 2018)

When rare species are not important: linking plot-based vegetation classifications and landscape-scale mapping in Australian savanna vegetation - E. Addicott; S. Laurance; M. Lyons; D. Butler; J. Neldner (Community Ecology, 2018)

Chromatographic fingerprinting of Lupinus luteus L. (Leguminosae) main secondary metabolites: a case of domestication affecting crop variability - Claudia E. Osorio; Veronique S. E. Amiard; Javiera Aravena-Calvo; Joshua A. Udall; Jeff J. Doyle; Iván J. Maureira-Butler (Genetic Resources and Crop Evolution, 2018)

Cortical and thalamic connectivity to the second auditory cortex of the cat is resilient to the onset of deafness - Blake E. Butler; Alexandra de la Rua; Taylor Ward-Able; Stephen G. Lomber (Brain Structure and Function, 2018)

Combining otolith chemistry and telemetry to assess diadromous migration in pinkeye mullet, Trachystoma petardi (Actinopterygii, Mugiliformes) - Nathan G. Miles; Gavin L. Butler; Sandra L. Diamond; David P. Bishop; Dylan E. van der Meulen; Ivars Reinfelds; Chris T. Walsh (Hydrobiologia, 2018)

Lack of alarm calls in a gregarious bird: models and videos of predators prompt alarm responses but no alarm calls by zebra finches - Nicole E. Butler; Robert D. Magrath; Richard A. Peters (Behavioral Ecology and Sociobiology, 2017)

Productivity dominated by picoplankton in a macro‐tidal tropical estuary, Darwin Harbour - D. Purcell‐Meyerink; J. Fortune; E. C. V. Butler (New Zealand Journal of Botany, 2017)
Productivity around the tropical coast of North Australia has been considered to be dominated by phytoplankton. The phytoplankton encompasses a large taxon which, dependent on the source definition, can vary significantly. Traditionally, they would only include pelagic photosynthetic organisms (autotrophic), yet more recently the definition is being revised to include heterotrophic organisms. Recent advancements in oceanography over the past three decades have found the prevalence in the global ocean of cyanobacteria of sizes ranging from 0.5–1.5 µm. Two cyanobacterial genera Synechoccocus and Prochlorococcus are now recognised to dominate phytoplankton cell counts and biomass specifically in the oligotrophic tropical and subtropical oceans. This study is the first to identify the importance of picoplankton as a foremost contributor to productivity in a macro‐tidal ecosystem in Northern Tropical Australia. Picoplankton was found to be the dominant group of primary producers (> 99% or 6 × 10 9 cells/L) within the phytoplankton in Darwin Harbour during the dry season of 2013. The larger phytoplankton > 2 µm contributed ( 2 cells/L) of the population. This study further defines the influences on this dynamic system that would allow the picoplankton community to thrive, highlighting the complexity of this nitrogen‐limited system, where nutrient cycling, including nitrogen fixation mediated possibly through the microbial community, plays a pertinent role. Other environmental influences include spring tides, spatial variation and increased turbidity which benefits heterotrophy over autotrophy in this ecosystem.

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Biomechanical Characterisation of the Human Auricular Cartilages; Implications for Tissue Engineering - M. F. Griffin; Y. Premakumar; A. M. Seifalian; M. Szarko; P. E. M. Butler (Annals of Biomedical Engineering, 2016)

Biogeographic variability in the physiological response of the cold‐water coral L ophelia pertusa to ocean acidification - Samuel E. Georgian; Sam Dupont; Melissa Kurman; Adam Butler; Susanna M. Strömberg; Ann I. Larsson; Erik E. Cordes (Marine Ecology, 2016)
While ocean acidification is a global issue, the severity of ecosystem effects is likely to vary considerably at regional scales. The lack of understanding of how biogeographically separated populations will respond to acidification hampers our ability to predict the future of vital ecosystems. Cold‐water corals are important drivers of biodiversity in ocean basins across the world and are considered one of the most vulnerable ecosystems to ocean acidification. We tested the short‐term physiological response of the cold‐water coral Lophelia pertusa to three pH treatments (pH = 7.9, 7.75 and 7.6) for Gulf of Mexico (USA) and Tisler Reef (Norway) populations, and found that reductions in seawater pH elicited contrasting responses. Gulf of Mexico corals exhibited reductions in net calcification, respiration and prey capture rates with decreasing pH. In contrast, Tisler Reef corals showed only slight reductions in net calcification rates under decreased pH conditions while significantly elevating respiration and capture rates. These differences are likely the result of environmental differences (depth, pH, food supply) between the two regions, invoking the potential for local adaptation or acclimatization to alter their response to global change. However, it is also possible that variations in the methodology used in the experiments contributed to the observed differences. Regardless, these results provide insights into the resilience of L. pertusa to ocean acidification as well as the potential influence of regional differences on the viability of species in future oceans.

Using a model based fourth-corner analysis to explain vegetation change following an extraordinary fire disturbance - S. E. Venn; C. M. Pickering; S. A. Butler; A. D. Letten (Oecologia, 2016)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Eurasian snow cover variability and links to winter climate in the CMIP5 models - Jason C. Furtado; Judah L. Cohen; Amy H. Butler; Emily E. Riddle; Arun Kumar (Climate Dynamics, 2015)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.

Analytic laboratory performance of a point of care urine culture kit for diagnosis and antibiotic susceptibility testing - E. Bongard; N. Frimodt-Møller; M. Gal; M. Wootton; R. Howe; N. Francis; H. Goossens; C. C. Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Marker assisted separation of resistance genes Rph22 and Rym16 Hb from an associated yield penalty in a barley: Hordeum bulbosum introgression line - Paul A. Johnston; Vijitha Meiyalaghan; Merle E. Forbes; Antje Habekuß; Ruth C. Butler; Richard Pickering (Theoretical and Applied Genetics, 2015)

Quantifying Florida Bay Habitat Suitability for Fishes and Invertebrates Under Climate Change Scenarios - Kelly A. Kearney; Mark Butler; Robert Glazer; Christopher R. Kelble; Joseph E. Serafy; Erik Stabenau (Environmental Management, 2015)

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Agronomic factors affect powdery scab of potato and amounts of Spongospora subterranea DNA in soil - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister; Steve M. Thomas; Denis Curtin (Australasian Plant Pathology, 2014)

Genetic diversity and population structure of sickleweed (Falcaria vulgaris; Apiaceae) in the upper Midwest USA - Sarbottam Piya; Madhav P. Nepal; Jack L. Butler; Gary E. Larson; Achal Neupane (Biological Invasions, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Porcine reproductive and respiratory syndrome (PRRS): an immune dysregulatory pandemic - J. E. Butler; K. M. Lager; William Golde; Kay S. Faaberg; Marek Sinkora; Crystal Loving; Y. I. Zhang (Immunologic Research, 2014)

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

CFSv2 ensemble prediction of the wintertime Arctic Oscillation - Emily E. Riddle; Amy H. Butler; Jason C. Furtado; Judah L. Cohen; Arun Kumar (Climate Dynamics, 2013)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Influence of fracture anisotropy and lithological heterogeneity on wellfield response in a fluvial sandstone aquifer of the Carboniferous Moncton Subbasin, Canada - Aaron J. DesRoches; Karl E. Butler; Shaun Pelkey (Hydrogeology Journal, 2013)

Fire, soil fertility and delayed seed release: a community analysis of the degree of serotiny - Peter J. Clarke; Kirsten E. J. Knox; Damian Butler (Evolutionary Ecology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Blueberry supplementation induces spatial memory improvements and region-specific regulation of hippocampal BDNF mRNA expression in young rats - Catarina Rendeiro; David Vauzour; Rebecca J. Kean; Laurie T. Butler; Marcus Rattray; Jeremy P. E. Spencer; Claire M. Williams (Psychopharmacology, 2012)

Linkage haplotype for allotypic variants of porcine IgA and IgG subclass genes - A. Kloep; N. Wertz; M. Mendicino; J. Ramsoondar; J. E. Butler (Immunogenetics, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Low amounts of Spongospora subterranea sporosorus inoculum cause severe powdery scab, root galling and reduced water use in potato (Solanum tuberosum) - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister (Australasian Plant Pathology, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Changes in Tundra Pond Limnology: Re-sampling Alaskan Ponds After 40 Years - Vanessa L. Lougheed; Malcolm G. Butler; Daniel C. McEwen; John E. Hobbie (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Skeletal muscle telomere length in healthy, experienced, endurance runners - Dale E. Rae; Alban Vignaud; Gillian S. Butler-Browne; Lars-Eric Thornell; Colin Sinclair-Smith; E. Wayne Derman; Mike I. Lambert; Malcolm Collins (European Journal of Applied Physiology, 2010)

The Fire Learning Network: A Promising Conservation Strategy for Forestry - Bruce E. Goldstein; William H. Butler; R. Bruce Hull (Journal of Forestry, 2010)
Conservation Learning Networks (CLN) are an emerging conservation strategy for addressing complex resource management challenges that face the forestry profession. The US Fire Learning Network (FLN) is a successful example of a CLN that operates on a national scale. Developed in 2001 as a partnership between The Nature Conservancy, the US Forest Service, and land-management agencies of the US Department of the Interior, the FLN has solicited the participation of fire professionals from more than 600 partner organizations to collaboratively design and implement ecological fire restoration strategies. Our review of the FLN provides evidence of the network's ability to improve conservation practices, points to its potential to transform and empower fire management practices and institutions on a national scale, and illustrates the utility of CLNs for other natural resource management challenges.

Patterns of Tamarix water use during a record drought - Jesse B. Nippert; James J. Butler; Gerard J. Kluitenberg; Donald O. Whittemore; Dave Arnold; Scott E. Spal; Joy K. Ward (Oecologia, 2010)

Influences of forest harvest and environmental gradients on aquatic invertebrate communities of seasonal ponds - Mark A. Hanson; Shane E. Bowe; Fred G. Ossman; John Fieberg; Malcolm G. Butler; Richard Koch (Wetlands, 2009)

An in vivo model of melanoma: treatment with ATP - Nicholas White; Gillian E. Knight; Peter E. M. Butler; Geoffrey Burnstock (Purinergic Signalling, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Use of weighted reference panels based on empirical estimates of ancestry for capturing untyped variation - Matthew R. L. Egyud; Zofia K. Z. Gajdos; Johannah L. Butler; Sam Tischfield; Loic Le Marchand; Laurence N. Kolonel; Christopher A. Haiman; Brian E. Henderson; Joel N. Hirschhorn (Human Genetics, 2009)

Porcine IgG: structure, genetics, and evolution - J. E. Butler; Nancy Wertz; Nicholas Deschacht; Imre Kacskovics (Immunogenetics, 2009)

Porcine IgG: structure, genetics and evolution - J. E. Butler; Nancy Wertz; Nicolas Deschacht; Imre Kacskovics (Immunogenetics, 2009)

Relationship between pancreatic vesicular monoamine transporter 2 (VMAT2) and insulin expression in human pancreas - Yoshifumi Saisho; Paul E. Harris; Alexandra E. Butler; Ryan Galasso; Tatyana Gurlo; Robert A. Rizza; Peter C. Butler (Journal of Molecular Histology, 2008)

Invertebrate community variation in seasonal forest wetlands: Implications for sampling and analyses - Anthony T. Miller; Mark A. Hanson; James O. Church; Brian Palik; Shane E. Bowe; Malcolm G. Butler (Wetlands, 2008)

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris) - Kim Valentine; Deborah A. Duffield; Lorelei E. Patrick; David R. Hatch; Virginia L. Butler; Roberta L. Hall; Niles Lehman (Conservation Genetics, 2008)

Genetic inactivation of acetylcholinesterase causes functional and structural impairment of mouse soleus muscles - A. Vignaud; F. Fougerousse; E. Mouisel; N. Guerchet; C. Hourde; F. Bacou; G. S. Butler-Browne; A. Chatonnet; A. Ferry (Cell and Tissue Research, 2008)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Reproductive biology of the endangered Oxleyan pygmy perch Nannoperca oxleyana Whitley - J. T. Knight; G. L. Butler; P. S. Smith; R. N. E. Wager (Journal of Fish Biology, 2007)
The reproductive biology of the Oxleyan pygmy perch Nannoperca oxleyana is described from simultaneous studies of wild populations in north‐eastern New South Wales and mature fish held in aquaria. In the wild, 50% of males and females matured at total lengths of 24·0–25·9 and 28·0–29·9 mm, respectively. The species displays sexual dichromatism during the spawning season, with males developing more intense red and brown fin and body colouration, and black pelvic fins. Captive male broodfish displayed territoriality during the breeding season, closely guarding sites within artificial, plant‐like substrata in which pairs of fish spawned adhesive eggs. Protracted serial spawning of wild and captive fish occurred from September to April and May at mean water temperatures ≥16·6° C and day length ≥10·7 h. Captive broodfish spawned on an average of 57% of days during the 256 day spawning period. Gonado‐somatic indices averaged 0·7% for all ripe males and 4·1–4·2% for all ripe females collected. Mean total and batch fecundities of captive females were 1323 eggs per fish and 7·8 eggs per fish per day, respectively, and relative fecundity was 587 eggs g −1 of body mass. Batch fecundity of wild females was estimated at 7·8 eggs per fish. The adaptive significance of this reproductive strategy in a harsh, variable environment is discussed.

The isolator piglet: a model for studying the development of adaptive immunity - J. E. Butler; Marek Šinkora (Immunologic Research, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Mechanism for proliferation inhibition by various selenium compounds and selenium-enriched broccoli extract in rat glial cells - Jan-Ying Yeh; Bor-Rung Ou; Yu-Chuan Liang; Joel Burchfiel; Judy A. Butler; Neil E. Forsberg; Philip D. Whanger (BioMetals, 2006)

The origin of activity in the biceps brachii muscle during voluntary contractions of the contralateral elbow flexor muscles - Inge Zijdewind; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2006)

Free-range Village Chickens on the Accra Plains, Ghana:Their Husbandry and Productivity - P. A. T. Aboe; K. Boa-Amponsem; S. A. Okantah; E. A. Butler; P. T. Dorward; M. J. Bryant (Tropical Animal Health and Production, 2006)

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)

Cooperation during prey digestion between workers and larvae in the ant, Pheidole spadonia - D. L. Cassill; J. Butler; S. B. Vinson; D. E. Wheeler (Insectes Sociaux, 2005)

Human melanomas express functional P2X7 receptors - Nicholas White; Peter E. M. Butler; Geoffrey Burnstock (Cell and Tissue Research, 2005)

Pedigree selection for Gibberella ear rot resistance in maize - Daniel A. Presello; Lana M. Reid; Gail Butler; Diane E. Mather (Euphytica, 2005)

Effects of dietary supplementation with vitamins C and E on muscle function during and after eccentric contractions in humans - A. Shafat; P. Butler; R. L. Jensen; A. E. Donnelly (European Journal of Applied Physiology, 2004)

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)

Buccal cells as a source of DNA for comparative animal genomic analysis - R. Brooks; J. Williamson; A. Hensley; E. Butler; G. Touchton; E. Smith (Biotechnology Letters, 2003)

Susceptibility of potato (Solanum tuberosum) cultivars to powdery scab (caused by Spongospora subterranea f. sp. subterranea), and relationships between tuber and root infection - Richard E. Falloon; Russell A. Genet; Andrew R. Wallace; Ruth C. Butler (Australasian Plant Pathology, 2003)

The Use of Inverse Phase Gas Chromatography to Measure the Surface Energy of Crystalline, Amorphous, and Recently Milled Lactose - Helen E. Newell; Graham Buckton; David A. Butler; Frank Thielmann; Daryl R. Williams (Pharmaceutical Research, 2001)

Sunshine records from Ireland: cloud factors and possible links to solar activity and cosmic rays - E. Pallé; C.J. Butler (International Journal of Climatology, 2001)
The records of sunshine hours obtained since the late 19th century from four stations distributed throughout Ireland were analysed. A gradual decrease in sunshine hours has occurred at all four sites since records began. Increasing cloud factors, resulting from enhanced evaporation rates over the Atlantic as sea surface temperatures have risen, is one possible explanation for the decline in sunshine. A strong negative correlation was confirmed between sunshine factors from ground‐based observations and satellite‐based cloud factors over Ireland. In addition, it was found that cloud factors over Ireland correlated well with cloud factors over large oceanic areas such as the North Atlantic and mid‐high latitudes generally. Thus cloud factors (and similarly sunshine factors) from regions on the boundaries of large oceans which lie in the direction of the prevailing wind could be useful in determining the long‐term changes in cloud factors over more extended areas. Knowledge of such long term variability in the Earth's cloud cover is important input information for modelling past climate change. The importance of cosmic rays as a link between solar activity and climate was assessed from a study of the ISCCP‐D2 satellite cloud factors and Irish sunshine data. Whilst these results confirmed the strong correlation between total cloud factor and cosmic rays over non‐tropical oceans between 1984 and 1991 previously reported, it was found that this correlation did not hold in the subsequent period 1991–1994. Other work has established a link through specifically low cloud. Indirect evidence of cloud formation by cosmic rays from a variation in the sunshine factor following Forbush decreases, and over the sunspot cycle, was mostly negative. Although a dip at seven years past sunspot minimum is evident in the sunshine factor for all four sites and in most seasons, it is of marginal statistical significance. Copyright © 2001 Royal Meteorological Society

Changes in muscle afferents, motoneurons and motor drive during muscle fatigue - Janet L. Taylor; Jane E. Butler; S. C. Gandevia (European Journal of Applied Physiology, 2000)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

Opposite changes in myosin heavy chain composition of human masseter and biceps brachii muscles during aging - M. Monemi; P.-O. Eriksson; F. Kadi; G. S. Butler-Browne; L.-E. Thornell (Journal of Muscle Research and Cell Motility, 1999)

Thermoregulation during swimming and diving in bottlenose dolphins, Tursiops truncatus - D. P. Noren; T. M. Williams; P. Berry; E. Butler (Journal of Comparative Physiology B, 1999)

Cellular adaptation of the trapezius muscle in strength-trained athletes - Fawzi Kadi; Anders Eriksson; Staffan Holmner; Gillian S. Butler-Browne; L.-E. Thornell (Histochemistry and Cell Biology, 1999)

The β enolase subunit displays three different patterns of microheterogeneity in human striated muscle - T. Merkulova; L-E. Thornell; G. Butler-Browne; C. Oberlin; M. Lucas; N. Lamandé; M. Lazar; A. Keller (Journal of Muscle Research and Cell Motility, 1999)

Corpuscles of Stannius and stanniocalcin-like immunoreactivity in the white sucker ( Catostomus commersoni ): evidence for a new cell-type - D. H. Zhang; G. Y. Oudit; L. E. Marra; D. G. Butler; J. H. Youson (Cell and Tissue Research, 1998)

Neuronal activity in the monkey ventrolateral thalamus following perturbations of voluntary wrist movements - E. G. Butler; Michael C. Harvey; David I. Finkelstein; Malcolm K. Horne (Experimental Brain Research, 1998)

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)

Effect of contraction strength on responses in biceps brachii and adductor pollicis to transcranial magnetic stimulation - J. L. Taylor; Gabrielle M. Allen; Jane E. Butler; S. C. Gandevia (Experimental Brain Research, 1997)

Sequence analysis of pig switch ? , C? , and C?m - Jishan Sun; J. E. Butler (Immunogenetics, 1997)

Genetic polymorphism of the IGHG3 gene in cattle - H. Rabbani; William R. Brown; John E. Butler; Lennart Hammarström (Immunogenetics, 1997)

The effect of thyroid hormones on the aerobic development of locomotor and cardiac muscles in the barnacle goose - K. E. Deaton; C. M. Bishop; P. J. Butler (Journal of Comparative Physiology B, 1997)

Phenotypic and genotypic stability of multiple lines of transgenic pigs expressing recombinant human protein C - Kevin E. Van Cott; Henryk Lubon; Christopher G. Russell; Stephen P. Butler; F.C. Gwazdauskas; James Knight; William N. Drohan; William H. Velander (Transgenic Research, 1997)

Differentiation of a rapidly growing, scotochromogenic, polycyclic-aromatic-hydrocarbon-metabolizing strain of Mycobacterium sp. from other known Mycobacterium species - Fatemeh Rafii; W. Ray Butler; Carl E. Cerniglia (Archives of Microbiology, 1992)

Hypoxic stress inhibits aerobic wound-induced resistance and activates hypoxic resistance to bacterial soft rot - Michael E. Vayda; Lyudmil S. Antonov; Z. Yang; William O. Butler; George H. Lacy (American Journal of Potato Research, 1992)

Stress or heat shock protein synthesis and cellular filamentation in psychrophilic and psychrotrophic bacteria - Kirk L. McCallum; Barbara J. Butler; William E. Inniss (Archives of Microbiology, 1989)

Methyl parathion persistence in soil following simulated spillage - L. C. Butler; D. C. Staiff; J. E. Davis (Archives of Environmental Contamination and Toxicology, 1981)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)